Protocol for a prospective observational cohort study of cutaneous leishmaniasis in Ethiopia [version 2; peer review: 2 approved, 1 approved with reservations] - Fewzia Shikur Mohammed; Amel Beshir Mohammed; Shimelis Doni Nigusse; Feleke Tilahun Zewdu; Abebaw Yeshambel Alemu; Teklu Cherkose; Kidist Bobosha; Eshetu Molla; Iris Mosweu; Vanessa Yardley; Saba Maria Lambert; Mirgissa Kaba; et al. (NIHR Open Research)
Background Cutaneous leishmaniasis (CL) is a skin neglected tropical disease, with an estimated 40,000 new cases each year in Ethiopia. CL causes ulcers, nodules, and plaques on the skin, and in some instances the destruction of the nasopharyngeal mucosa and cartilage. Some CL lesions may heal spontaneously, whilst other lesions may require therapies which are associated with discomfort, adverse effects, prolonged treatment, and a frequent lack of a complete response. Scarring, a sequela of CL, causes permanent disfigurement and is associated with stigma linked with a reduction in health-related quality of life. The choice of treatment for CL is based upon factors including the causative species; the number, extent, size, and location of lesions; and the availability of treatments. The development of robust evidence for CL treatment is hindered by a lack of validated and appropriate outcome measures and few data to support hypothesis-generation and trial design. There is a paucity of prospective data with well-defined treatment outcomes for CL caused by L. aethiopica. Aim The overall aim of this study is to improve the understanding of the health and economic burden of CL. Methods We have designed an observational, multi-centre cohort study to examine treatment outcomes for CL in Ethiopia which includes clinical outcomes, laboratory outcomes, patient reported outcome measures, scar assessments and cost effectiveness. We aim to recruit up to 750 participants across two hospital sites. We present here the protocol for this cohort study with a 12-month follow up period for each participant. Conclusions These data will inform the design of randomized controlled trials to evaluate new treatment strategies, with appropriate economic evaluations. This will help improve evidence-based guidelines and support evidence-led policy decisions, not only in Ethiopia but also globally.